Fretting wear of metallic multilayer films - Haseeb, A.S. Md. Abdul; Celis, Jean Pierre; Roos, Jozef R. (Elsevier, 2003)
Fretting wear behaviour of electrodeposited Cu/Ni multilayer films with 10 and 5 nm thick sublayers has been investigated against a hardened steel ball as the counter body and compared with that of the constituents, Cu and Ni. The wear tests were carried out by using a ball-on-flat geometry at a translation frequency of 8 Hz and slip amplitude of 100 mum. Friction force was recorded on line during the tests. At the end of the tests, the wear scars were examined by laser surface profilometry, scanning electron microscopy and energy dispersive X-ray microanalysis. It has been observed that the frictional and wear mechanisms are very different for copper, nickel and Cu/Ni multilayers. Fretting of copper creates a relatively smooth wear scar mainly by mechanical ploughing of the asperities on steel counterbody (abrasive wear) and shows a very little third body interaction. Fretting of nickel involves adhesive wear resulting in a large transfer of steel to nickel, which is attributed to the strong chemical interaction between nickel and the steel counterbody. Fretting on multilayers involves a strong third body interaction resulting in ploughing mainly by debris (abrasive wear). The coefficient of friction is approximately 0.45 for copper, and approximately 0.8 for nickel as well as for multilayers. The values of the coefficient of friction for nickel and Cu/Ni multilayers found under the present fretting conditions are approximately double the corresponding values reported earlier for sliding wear conditions. It has been found that Cu/Ni multilayer is more resistance to fretting wear than the constituents, copper and nickel. Furthermore, the fretting wear resistance of Cu/Ni multilayers with 5 nm thick sublayer is better than that of the multilayers with 10 nm thick sublayers. (C) 2003 Elsevier B.V. All rights reserved.